Rekonstruksi Desain Kegiatan Laboratorium (DKL) pada Materi Bioteknologi dengan Pendekatan Saintifik - Naufal Ahmad Muzakki; Bambang Supriatno; Sri Anggraeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the design of laboratory activities on Biotechnology materials and carry out reconstruction. The method used is descriptive qualitative and sampling is done by purposive sampling with five DKL. The analysis conducted on DKL is measured in terms of components of competence, practicality and knowledge construction. The results showed that competence and knowledge construction components were still low and the practical components had been met. In conclusion, many DKL on Biotechnology material still cannot support competence and knowledge construction. Keywords: Design Analysis of Laboratory Activities, Biotechnology, Laboratory Activities